2022
DOI: 10.3892/ijo.2022.5439
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clock as a possible control point in colorectal cancer progression (Review)

Abstract: The circadian rhythm is generated at the cellular level by a molecular clock system that involves specific genes. Studies have revealed that circadian clock disruption is a control point in cancer progression. Colorectal cancer (CRC) is one of the cancers closely associated with circadian disruption. In the present review, the involvement of the circadian clock in CRC development was summarized. Abnormal expression of certain clock genes has been found in patients with CRC and their correlation with clinicopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 112 publications
1
6
0
Order By: Relevance
“…Seemingly contradictory findings were reported for BMAL1, which was shown to act both as an oncogene, as well as a tumour suppressor. This dual function of BMAL1 on carcinogenesis was also observed for other cancer entities such as colorectal cancer 34 .…”
Section: Impact Of the Circadian Clock On Gbm Cell Proliferation And ...supporting
confidence: 64%
“…Seemingly contradictory findings were reported for BMAL1, which was shown to act both as an oncogene, as well as a tumour suppressor. This dual function of BMAL1 on carcinogenesis was also observed for other cancer entities such as colorectal cancer 34 .…”
Section: Impact Of the Circadian Clock On Gbm Cell Proliferation And ...supporting
confidence: 64%
“…According to earlier research, chemotherapy and TIMELESS are highly connected in several types of human cancer [ 46 , 47 ]. TIMELESS is significantly connected with the susceptibility of numerous anti-cancer targeted treatment medications, including fludarabine, lapatinib, and 6-mercaptopurine, as this study’s findings have shown.…”
Section: Discussionmentioning
confidence: 99%
“…If the feedback loops are broken by irregular rest, diet or night shifts, the master switch of the normal circadian processes will become weak slowly. Then, the downstream pathophysiological processes are also out of control, such as cell cycle, cell apoptosis and cell metabolism, as well as invasion, metastasis and angiogenesis of CRC cells [10,31]. Circadian disruption and abnormal expression levels of circadian clock genes dysregulate these processes [6,32].…”
Section: The Effect Of Core Circadian Genes On Crcmentioning
confidence: 99%
“…Various physiological and pathological processes are closely related to circadian rhythm. Many studies [6][7][8][9] showed that circadian disruption was one of the endogenous factors resulting in tumour initiation and progression of various human malignancies, including colorectal cancer (CRC) [10,11]. CRC is one of the most common malignant tumours and the third most common cause of cancer death worldwide, with high morbidity and mortality [12,13].…”
Section: Introductionmentioning
confidence: 99%